Penerapan Teknologi Digital dalam Optimalisasi Konsep Ekonomi Sirkular Menuju Green Economy di Desa Blang Asan - Zainal, Zara Yunizar; Usrina, Nura; Ersa, Nanda Savira; Hasan, Phadlin; Arif H., Nanda Nan (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
und: Blang Asan Village, Peusangan Subdistrict, Bireuen Regency, faces serious challenges in waste management due to low public awareness and limited waste transportation facilities. To address this issue, the village government, in collaboration with BUMDes Asan Jaya and Asri Waste Bank, introduced the Integrated Waste Management (PST) program, supported by the Environmental and Forestry Office (DLHK) of Bireuen Regency. This program utilizes digital technology through the Beclean application and the development of composters for organic waste management. Method: The main activities include socialization, training, technology implementation, community mentoring, and the operation of an Android-based waste management application integrated with the Waste Bank. One of the technologies implemented in this program is the Beclean application, which aims to reduce the amount of waste sent to final disposal sites by utilizing the application for integrated waste management. The program is designed using the SMCR (Source, Message, Channel, Response) communication model to ensure effective information delivery and implementation. Results: Indicate increased community participation in recycling and a reduction in the volume of waste sent to final disposal sites (TPA). Additionally, it has created new economic value by processing waste into useful products. The program's sustainability is ensured through regular evaluations to maintain its positive impact on the community and support Clean and Healthy Living Behavior (PHBS), including empowering the community to recycle waste into economically valuable products. Conclusions: Through this initiative, it is hoped that a circular economy system can be realized, enhancing economic growth through household waste management while minimizing environmental damage.